Determining the Optimal Duration of Progesterone Supplementation prior to Transfer of Cryopreserved Embryos and Its Impact on Implantation and Pregnancy Rates: A Pilot Study. (26th September 2016) - Sharma, Sangita; Majumdar, Abha
Abstract : Objective. To determine the optimal duration of progesterone supplementation prior to transfer of cryopreserved embryos and its impact on implantation and pregnancy rates. Study Design . Prospective randomised study. Materials and Methods . In an IVF unit of a tertiary centre, sixty-six patients undergoing cryopreserved embryo transfer cycles were included. Endometrial preparation was done with estradiol valerate. Once it reached a minimum of 7 mm, patients were allocated randomly into group I (n = 39 ) and group II (n = 27 ). Injectable progesterone 100 mg daily was then started for 3 and 4 days, respectively. This was followed by transfer of at least one thawed cleavage stage day 2 embryo of good quality. Groups I and II were compared in terms of clinical pregnancy and implantation rates. Results . In group I (3-day progesterone) and group II (4-day progesterone) the pregnancy rates were 41.02% (16/39) and 18.51% (5/27), respectively. On the other hand, the implantation rates were 16.82% (18/107) and 7.69% (6/78), respectively. The difference was statistically significant (p values 0.0172 and 0.0386, resp.). Conclusion . Progesterone supplementation for three days before the transfer of cleavage stage (day 2) cryopreserved embryos has significantly higher pregnancy and implantation rates, as compared to four-day supplementation.